Better Britons : reproduction, national identity, and the afterlife of empire - Attewell, Nadine (University of Toronto Press, 2014)
Better Britons charts an innovative approach to the politics of reproduction by reading an array of works and discourses that reflect on the significance of reproductive behaviours for civic, national, and racial identities.